Fecal calprotectin levels in acute anterior uveitis in patients with spondyloarthritis - Gazim,Caio Cézar (2022)
ABSTRACT Purpose: This study measured fecal calprotectin levels in a series of patients with anterior uveitis in order to determine whether anterior uveitis patients with associated spondyloarthritis have higher levels of fecal calprotectin than patients with anterior uveitis of other etiologies. A third group of patients with spondyloarthritis without uveitis was also evaluated to understand the role of acute anterior uveitis in increasing fecal calprotectin. Methods: In this cross-sectional study, 28 patients were divided into three groups: (a) Group 1, spondyloarthritis and uveitis (n=9); (b) Group 2, spondyloarthritis without uveitis (n=10); and (c) Group 3, uveitis without spondyloarthritis (n=9). The levels of fecal calprotectin were determined. Results: Groups 1 and 2 showed higher median fecal calprotectin levels (101.0 and 93.0 µg/g, respectively) compared with Group 3 (9.0 µg/g) (p=0.02). However, no relationship between fecal calprotectin levels and the presence of uveitis with spondyloarthritis could be demonstrated. Conclusion: Patients with spondyloarthritis with or without acute anterior uveitis have significantly elevated levels of fecal calprotectin. This test may be useful for differentiating spondyloarthrit-associated uveitis from uveitis of other etiologies.